Development of Children’s Rights from the Second Part of the 20th Century in Vietnamese Private Law Compared to Chinese Private Law - Huynh Thi Truc, Giang; Nguyen Thi My, Linh (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
Since the Communist Party won the revolution in Vietnam on August 19, 1945 and, in China on October 1, 1949, the Socialist Republic of Vietnam and the People’s Republic of China were established. After that, the Governments of these two countries issued many documents to adjust the social relations in the new situation and realize the goal of bringing the society to develop towards the socialist orientation. Besides politics, economy, social security, the protection of children’s rights was also a concern by the authorities. The article examines the development of child protection regulations from the founding of the Socialist Republic of Vietnam and the People’s Republic of China. Considering analysis, evaluation and comparison of child protection regulations of these two countries, the article has highlighted the progress of each country’s legislation in each period.